Pengaruh Tax Payment Gateway Pajakku Terhadap Kepatuhan Wajib Pajak Pada Perusahaan Yang Terdaftar Di KPP Pratama Makassar Selatan - Alya Mutia; Amran; Endang Winarsih (Indonesian Journal of Taxation and Accounting, 2024)
The aim of this research is to obtain an overview of the effect of implementing the Tax Payment Gateway on tax compliance. This type of research uses quantitative research methods with an associative approach. The sample used was 44 corporate taxpayers registered with KPP Pratama South Makassar. The data for this research were taken from distributing questionnaires using non-probability sampling techniques. Based on the results of data research using SPSS 22, it shows that the Tax Payment Gateway system has t count > t table, that is, the results show that Ha is accepted. Data Analysis This research uses simple regression analysis to analyze the variables. The results of this simple linear regression analysis research show that the Tax Payment Gateway has a positive and significant effect on tax compliance.